Is there a role for menstrual cycle phased resistance training programmes for women post anterior cruciate ligament reconstruction? A scoping review protocol. (15th August 2022) - O'Loughlin, Emma; Reid, Duncan; Sims, Stacy
Abstract: Background: Women need to engage in effective quadriceps resistance training programmes following anterior cruciate ligament reconstruction. Recent research has supported follicular phase-based resistance training for enhancing resistance training strength outcomes in eumenorrheic females. It is unclear whether research has investigated menstrual cycle phased resistance training programs in eumenorrheic females post-ACLR or whether there is a gap for further research in this area. Objective: This scoping review aims to describe what is known about menstrual cycle phased resistance training programmes in injured and non-injured eumenorrheic females, identify any existing gaps in knowledge, and propose future research. Methods: The research team will search five databases using predetermined search terms. Eumenorrheic female participants undergoing a menstrual cycle phased resistance training programme for at least one menstrual cycle length will be included. All studies must be in the English language and published in academic journals. The research team will evaluate relevant titles and abstracts against the eligibility criteria. Potentially relevant sources will be retrieved in full. The full text of selected studies will be assessed in detail against the inclusion criteria by two reviewers. The research team will extract data from included papers using a data charting form. The review will present all results in table format accompanied by a narrative summary. Results: Results are not yet known. Discussion: This will contribute to the understanding of methodologies and outcomes of menstrual cycle phased resistance training programmes, and indicate whether there is a role for future research in injured and non-injured populations.